2022
DOI: 10.3390/plants11060802
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Use of Highly Adaptive Productive and Technological Red Currant Genotypes to Improve the Assortment and Introduction into Different Ecological and Geographical Zones

Abstract: Global climate change with the cyclicity of natural and climatic processes in the growing season of berry plants, causes weakening at the defense system to (a)biotic stressors, which actualize the need for accelerated cultivar-improving breeding. A new hybrid red currant material was obtained and studied by the method of interspecific hybridization. Correlation analysis was used to assess the relationship between adaptively significant and economical and biological traits. To assess intergenotypic variability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In the dendrogram created, the similarity rate of the genotypes was found to be in the range of 0.71-0. Previous studies conducted on different wild edible fruits showed that due to rich gene combination, those plants showed high genetic diversity and adaption (61)(62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…In the dendrogram created, the similarity rate of the genotypes was found to be in the range of 0.71-0. Previous studies conducted on different wild edible fruits showed that due to rich gene combination, those plants showed high genetic diversity and adaption (61)(62)(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…In connection with the mechanization of berry harvesting, traditional approaches to selecting cultivars and agricultural techniques are changing [17]. The essential characteristics of red and black varieties that meet the requirements for mechanical harvesting are the morphological characteristics of the bush, the yield, simultaneous ripening of the berries, the berry quality, resistance to biotic stresses (especially to Sphaerotheca mors-uvae, Cecidophyopsis ribis), duration of removable ripeness of berries, minimal damage to the bushes by a mechanized harvester [18][19][20][21]. Studies conducted mainly on black currant cultivars show the relationship between crop losses during mechanical harvesting and the harvest period and the prediction of harvesting duration.…”
Section: Introductionmentioning
confidence: 99%
“…The first red currant crops appeared at the beginning of the 15th century, and it was widely cultivated in gardens in the 16th century [4]. Red currant has become popular and spread as a result of the demand for berries due to their high therapeutic effect, as well as technological efficiency, and economically valuable characteristics [5]. Red currant provides healthful and delicious fruits which are a rich source of organic acids, vitamins, and phenolics with antioxidant and antiradical properties [6,7].…”
Section: Introductionmentioning
confidence: 99%